EFFECT OF LASER FORMING REPAIRING ON THE FOUR-POINT BENDING STRENGTH OF TITANIUM ALLOY I-SHAPED BEAM - ZHUO Yi; LV YuanBo; FAN YouYou; FAN JunLing (Jixie qiangdu)
The static and fatigue strength of laser forming repairing beam and forged beam were studied by four-point bending test,and the effect of laser forming repairing on the static and fatigue strength of TA15 titanium alloy beam was investigated. By contrast,laser forming repairing can generate dense and uniform metallurgical bonded interface zone in the repaired area of metal base,which make the similar static and fatigue strength between repaired beam and forged beam,and this technology would provide strong support for the repairing of crucial part.